Chicomexochitl y el maíz entre los nahuas de Chicontepec: la continuidad del ritual - Victoriano de la Cruz Cruz (Ksiegarnia Akademicka Publishing, 2021)
The cultivation and veneration of corn is central to all Mesoamerican cultures. Long before the Spaniards arrived indigenous people worshiped corn and pleaded for each harvest to be as good as the preceding one. Today’s Nahuas consider corn sacred and never permit it to lie on the ground: it must always be protected and sheltered. The Nahuas of Chicontepec, Veracruz continue to dance and pray to the corn deity, Chicomexochitl “Seven Flower”. This paper reveals the continuity of ritual practices and symbolism relating to the worship of maize in Nahua culture from prehispanic times to the present. It is based on the sixteenth‑century written sources, recent anthropological studies, and my own fieldwork associated with the Chicomexochitl ritual.